rhBMP-2-loaded hydroxyapatite/beta-tricalcium phosphate microsphere/hydrogel composite promotes bone regeneration in a novel rat femoral nonunion model - Kitahara, Takayuki; Tateiwa, Daisuke; Hirai, Hiromasa; Ikuta, Masato; Furuichi, Takuya; Bun, Masayuki; Ukon, Yuichiro; Kanie, Yuya; Furuya, Masayuki; Fujimori, Takahito; Okada, Seiji; Kaito, Takashi (Frontiers in Bioengineering and Biotechnology, 2024)
Background Nonunion following fracture treatment remains a significant clinical challenge, adversely affecting the patient’s quality of life and imposing a substantial economic burden. The emergence of bone morphogenetic protein 2 (BMP-2) for bone regeneration represents a promising avenue, albeit limited by side effects such as inflammatory reactions primarily due to suboptimal drug delivery systems. This study focuses on NOVOSIS putty (NP), a novel biomaterial designed for the sustained release of BMP-2, aiming to mitigate these limitations and enhance bone healing. Objective This research aimed to evaluate the effectiveness of NP, a hydroxyapatite granules/β-tricalcium phosphate hydrogel composite (HA/β-TCP/hydrogel), as a BMP-2 carrier for promoting bone regeneration in a new rat nonunion model of long bone. Methods Using Sprague Dawley rats, a 2-mm silicone disk was interposed at the femoral fracture site, and intramedullary fixation with K-wire was performed to create a nonunion with a 2-mm bone defect. After 3 weeks, internal fixation with a plate, removal of the silicon disk, and refreshing the nonunion site were performed by implanting three different materials into the nonunion sites: allogenic iliac bone (IB), collagen sponge (CS) containing 10 μg of BMP-2, or NP containing 10 μg of BMP-2. Bone healing was evaluated weekly using micro-computed tomography (CT); ex vivo micro-Ct and histological evaluation were conducted at 6 weeks. Results At 6 weeks, NP demonstrated a significantly higher bone union rate (76.5%) compared with the CS group (35.3%, p = 0.037), and the IB group (6.3%, p < 0.0001). Bone mineral density (BMD) and bone volume/tissue volume (BV/TV) were also significantly higher in the NP group compared with the CS group (BMD, p < 0.0001; BV/TV, p = 0.031). Histological analysis showed the fracture gap in the NP group was filled with more trabecular bone and less fibrous tissue compared with the CS group. Conclusion The study confirms NP is a highly effective BMP-2 carrier, significantly improving bone union rates and new bone formation in nonunion fractures. The sustained release of BMP-2 from the hydrogel component reduced inflammatory responses and enhanced bone regeneration. NP can be a promising alternative to collagen-based BMP-2 delivery systems.